Achieving balanced cocrystals of energetic materials via coagglomeration and their applications - Patil, Veerabhadragouda B. (Univerzita Pardubice, 2024)
Earlier reported methods for cocrystallization of EMs especially nitramines are lacking with selectivity and scalability. When it comes to adoption to industrial scale production of energetic-energetic cocrystals (EECCs) it’s more difficult. We made thorough literature survey and developed method of coagglomeration for attractive nitramines via solvent mediated slurry method; in which Co-agglomeration of the co-precipitated micro-particles of nitramines themselves or with polynitroarenes by the slurry method is a unique crystal engineering approach to modify the energetic properties of attractive nitramines like CL20, HMX, BCHMX, RDX etc. The properties and structural modification in the 60+ co-agglomerated crystals (CACs) newly prepared in our laboratory. There are notable variations in the crystal morphologies and packing of crystals, including key properties like relatively high density, melting point, impact sensitivity, and detonation properties. These CACs are in the overwhelming majority showing properties like co-crystals. Apart from these aspects, co-agglomeration provides a huge opportunity to tune the key properties and performance of existing energetic materials and is easy to scale-up for the industrial level. These preliminary results also suggest that chemical engineering factors are involved in the preparation of CACs, as in conventional crystallization. The optimization of them should be a matter of downstream technological research.
Dosažení vyvážených kokrystalů energetických materiálů koaglomerací a jejich aplikace
Keywords: nitramines; co-agglomeration; co-crystals; impact sensitivity; detonation parameters; nitraminy; ko-aglomerace; ko-krystaly; citlivost na náraz; detonační parametry